WOMEN IN THE PROFESSIONAL LABOR MARKET OF RUSSIAN UNIVERSITY TEACHERS - Ilina, Irina; Nakhratova, Evgeniya; Buley, Natalia; Matanis, Victoria; Vasilyuk, Tatyana (Revista Inclusiones, 2020)
The article analyzes the situation of women in the professional labor market of university teachers in the context of modernization of higher education. The main trends in the transformation of the higher school personnel in Russia are distinguished taking into account gender factors. The dynamics of indicators characterizing the number and professional and qualification characteristics of teachers in Russian universities are presented and the gender structure of university research and pedagogical staff is analyzed. Based on the results of sociological studies, including a survey, conducted independently by the authors, the following indicators have studied: dynamics of working conditions, organization of the educational process and professional motivation of women teachers. The authors propose a model for segmenting the labor market of women teachers, in which the main criteria are labor efficiency and the competitiveness of women teachers. The objective and subjective factors causing the emergence of gender disparities in the higher-education teaching personnel, as well as the causes of unequal access